2020
DOI: 10.2147/opth.s248787
|View full text |Cite
|
Sign up to set email alerts
|

<p>High-Resolution Wavefront-Guided Photorefractive Keratectomy and Accelerated Corneal Crosslinking for Stabilization and Visual Rehabilitation of Keratoconus Eyes</p>

Abstract: Purpose: To evaluate the visual and refractive outcomes after high-resolution wavefrontguided (HRWG) surface ablation with corneal crosslinking (CXL) in keratoconus eyes. Patients and Methods: In this prospective, interventional case series, 47 eyes of 28 progressive keratoconus patients older than age 18 were enrolled. All patients underwent HRWG photorefractive keratectomy (PRK) with simultaneous accelerated CXL. The study parameters were manifest refraction spherical equivalent (MRSE), keratometric outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Tamayo et al [ 19 ] conducted a pilot study examining at wavefront-guided PRK along with simultaneous ACXL in patients with KC. High-order aberrations do play an important role in reduced visual acuity.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tamayo et al [ 19 ] conducted a pilot study examining at wavefront-guided PRK along with simultaneous ACXL in patients with KC. High-order aberrations do play an important role in reduced visual acuity.…”
Section: Reviewmentioning
confidence: 99%
“…At the end of their study, Tamayo et al reported insignificant improvements in HOA, including mean coma, spherical aberration, and total root mean square (RMS). These improvements, however, did lead to significant improvements in mean UDVA, mean CDVA, and keratometric readings [ 19 ]. Findings from Tamayo et al suggest that wavefront-guided interventions have the potential to target HOAs.…”
Section: Reviewmentioning
confidence: 99%
“…As CXL leads to gradual changes in the anterior corneal curvature for up to a year postoperatively, there is a valid question over the exact refraction target in combined procedures. Nonetheless, promising results are still observed in specific protocols without any adjustment for such refractive changes ( 229 ).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A very important paper from John Kanelopoulus [65], brought the term Athens Protocol to ophthalmology, that popularized this type of combined treatment soon after. Two papers have been published with our own results [66,67].…”
Section: Treatment Of Keratoconus: Historymentioning
confidence: 99%